2019
DOI: 10.1186/s13018-019-1350-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravoxel incoherent motion diffusion-weighted MR imaging and magnetic resonance spectroscopy in differentiation between osteoporotic and metastatic vertebral compression fractures

Abstract: Purpose Our purpose was to combine intravoxel incoherent motion diffusion-weighted MR imaging (IVIM-DWI) and magnetic resonance spectroscopy (MRS) to differentiate osteoporotic fractures from osteolytic metastatic vertebral compression fractures (VCFs). Methods A total of 70 patients with VCFs were included and divided into two groups, according to their causes of fractures based on pathological findings or clinical follow-up. All patients underwent conventional sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The number of studies that assess the value of IVIM and DK in the differentiation of benign and malignant musculoskeletal tumors is fewer than those using the monoexponential diffusion model. [8][9][10][11][12][13][14][15][16][17][18][19] In this study, we found a statistically significant difference in D ivim-min between benign and malignant tumors in the "all tumors" group and in the nonmyxoid and nonchondroid tumor subgroup. The best cut-off value was 0.999 Â 10 À3 mm 2 s À1 for D ivim-min in both tumor groups.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The number of studies that assess the value of IVIM and DK in the differentiation of benign and malignant musculoskeletal tumors is fewer than those using the monoexponential diffusion model. [8][9][10][11][12][13][14][15][16][17][18][19] In this study, we found a statistically significant difference in D ivim-min between benign and malignant tumors in the "all tumors" group and in the nonmyxoid and nonchondroid tumor subgroup. The best cut-off value was 0.999 Â 10 À3 mm 2 s À1 for D ivim-min in both tumor groups.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the interobserver and intraobserver agreement was moderate for f min and poor for D* min . In the current literature, most of the studies, which assess the value of IVIM-derived parameters in musculoskeletal tumors are performed at 3 T, and ICCs varied between 0.83-0.947 for D* and 0.81-0.957 for f. [8][9][10]13,18 In one exceptional study which was performed at 3 T ICCs were 0.386-0.764 for D* and 0.588-0.841 for f. 11 In one study performed at 1.5 T with 12 b values (9 b values < 200 mm 2 s À1 ), ICCs were 0.786 for D* and 0.701 for f, 8 which were lower than many of the studies conducted at 3 T, yet still higher than our findings. The discrepancy with our results might be related to lower SNR due to our lower field strength, lower number of b values (11 b values and 8 of them < 200 mm 2 s À1 ), and possibly lower averages used in order to keep the overall examination time as short as possible (b values/averages: 0/2, 10/2, 20/2, 40/2, 50/2, 75/2, 100/2, 150/2, 300/2, 500/2, and 800/8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the follow-up period is relatively short, while a longer follow-up time is necessary to determine the risk factors for height loss of treated vertebral bodies after PVP. Some new technologies, such as combined intravoxel incoherent motion diffusion-weighted MR imaging and magnetic resonance spectroscopy, have not been employed to differentiate osteoporotic fractures from osteolytic metastatic vertebral compression fractures in this study [ 41 ]. Finally, every patient’s daily activity is not controlled entirely in follow-up period after PVP.…”
Section: Limitationsmentioning
confidence: 99%